Emphatische Subjektanzeige in der deutschen und polnischen Textstruktur - Gaca, Alicja (Studia Germanica Posnaniensia, 2018)
Emphasizing (Emphase, Hervorhebung) of the relevance of some fragment of a text (here of an object in particular) is considered as semantic relation (=dissimilativer Konnektor) and its formal exponents interpreted from the point of view of the syntax of the text. It is an attempt at establishing the rules of equivalence for both languages. The knowledge of conventions (rules of usa.ge) which control communicative structure of the text in German and in Polish is a precondition of proper reception (in communicative and stylistic sense) and text translation.